2008
DOI: 10.1590/s0100-40422008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and vitamin content of beef, chicken, and turkey hydrolysates mineral and vitamin content of protein hydrolysates

Abstract: Recebido em 20/10/06; aceito em 29/6/07; publicado na web em 19/12/07The purpose of this study was to assess the concentration of vitamins and minerals in meat protein hydrolysates. Calcium, phosphorus and iron were analyzed by inductively coupled-plasma atomic emission spectrophotometry; vitamin C was analyzed by the reduction of cupric ions and vitamins B1 and B2 by fluorescence. Regarding minerals, the beef hydrolysate (BH) had more iron than the turkey hydrolysate (TH) and the chicken hydrolysate (CH); TH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…Even though chicken is known as a good source of protein, the mineral content in chicken is said to be lower compared to cattle meat. Another research showed that chicken meat contained much lower Calcium (Ca), Magnesium (Mg), and Iron (Fe) [4,28]. Another essential mineral, Zinc (Zn) is also found to be lower in chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…Even though chicken is known as a good source of protein, the mineral content in chicken is said to be lower compared to cattle meat. Another research showed that chicken meat contained much lower Calcium (Ca), Magnesium (Mg), and Iron (Fe) [4,28]. Another essential mineral, Zinc (Zn) is also found to be lower in chicken meat.…”
Section: Introductionmentioning
confidence: 99%